The Influence of Trust, Security and Service Quality on Purchasing Decisions: (Study on Zalora Indonesia Online Shop Application Consumers in Tangerang) - Rina Ayu Vildayanti; Imanuel Rahul (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study aims to determine the effect of Trust, Security, and Quality of service on consumer Purchasing Decisions in Application online shop Zalora Indonesia in Tangerang. This type of research is quantitative methode. The sample used was 100 respondens with a sampling methode using non-probability sampling with accindetal technique. The data collection technique was through a questionnaire with a likert scale which had been processed using SPSS sofware version 26. The result of this study indicate that the sequrity and quality of service variables each have a significant effect on purchasing decision, while the trust variable has no significant effect on purchasing decisions